Corticospinal responses during passive shortening and lengthening of tibialis anterior and soleus in older compared to younger adults. Issue 3 (7th February 2020) - Škarabot, Jakob; Ansdell, Paul; Howatson, Glyn; Goodall, Stuart; Durbaba, Rade
Abstract : New Findings: What is the central question of this study? Are there age‐related differences in corticospinal responses whilst passively changing muscle length? What is the main finding and its importance? In contrast to young, older adults exhibited no modulation of corticospinal excitability in tibialis anterior during passive ankle movement. These data show impaired sensorimotor response in older adults during length changes of tibialis anterior, thus contributing to our understanding of age‐related changes in sensorimotor control. Abstract: Corticospinal responses have been shown to increase and decrease with passive muscle shortening and lengthening, respectively, as a result of changes in muscle spindle afferent feedback. The ageing sensory system is accompanied by a number of alterations that might influence the processing and integration of sensory information. Consequently, corticospinal excitability might be modulated differently whilst changing muscle length. In 10 older adults (66 ± 4 years), corticospinal responses (MEP/Mmax ) were evoked in a static position, and during passive shortening and lengthening of soleus (SOL) and tibialis anterior (TA), and these data were compared to the re‐analysed data pool of 18 younger adults (25 ± 4 years) published previously. Resting motor threshold was greater in SOL compared to TA ( P < 0.001), but did not differ between young and older ( P = 0.405). No differences were observed in MEP/Mmax between the static position, passive shortening or lengthening in SOL (young: all 0.02 ± 0.01; older: 0.05 ± 0.04, 0.03 ± 0.02 and 0.04 ± 0.01, respectively; P = 0.298), and responses were not dependent on age ( P = 0.090). Conversely, corticospinal responses in TA were modulated differently between the age groups ( P = 0.002), with greater MEP/Mmax during passive shortening (0.22 ± 0.12) compared to passive lengthening (0.13 ± 0.10) and static position (0.10 ± 0.05) in young ( P < 0.001), but unchanged in older adults (0.19 ± 0.11, 0.22 ± 0.11 and 0.18 ± 0.07, respectively; P ≥ 0.867). The present experiment shows that length‐dependent changes in corticospinal excitability in TA of the young are not evident in older adults. This suggests impaired sensorimotor response during muscle length changes in older age that might only be present in ankle flexors, but not extensors. Abstract :